Development and validation of an X-ray model for an Elekta Precise multileaf collimator to be used in Monte Carlo dose calculations - Smit, Jacobus Johannes Lodewikus (University of the Free State, 2015)
Linear accelerators (Linacs) produce megavoltage (MV) energy photon and electron beams to irradiate tumour volumes in patients. More complex field shapes can be setup quickly with multileaf collimators (MLC’s), thus more advanced treatments like intensity-modulated radiation therapy (IMRT) are possible. This is one of the reasons why treatment planning models should be accurately commissioned and accurate dose calculation algorithms employed. Monte Carlo (MC) based dose calculations are very suitable to solve this issue. The aim of this project was to continue the development of an X-ray source model for MC dose calculations for an ElektaTM Precise MLC Linac. Methods & Materials An in-house developed graphical user interface (GUI) was used to calculate exit fluence based on a mathematical model and energy spectra derived from the Schiff formula. This produced an input source file for source number 4 in the DOSXYZnrc code. DOSXYZnrc was used to calculate X-ray dose distributions in water and RW3 solid water phantoms. These dose distributions were compared to actual measured film or water tank dose data. A gamma index was calculated to compare the MC and measured dose. The criteria used for the γ-index was 2 % dose / 2 mm distance-to-agreement. Dose distribution data for square, rectangular and off-set fields were compared. Results & Discussion Prior to source commissioning a GAFCHROMIC® EBT2 film dosimetry system, that entails using a film scanner, was setup. With the use of the EBT2 film, scanner properties like scanner uniformity, film orientation, film scanning side and repeatability were investigated. Film orientation produced the largest discrepancy of 3.5 % between portrait and landscape orientation. The remaining properties were within 1 % variation. A range of fields for 6, 8 and 15 MV beams were modelled, simulated and compared to corresponding measured water tank data. Parameters in the MC source model were adjusted until the gamma-index criteria were met for each comparison. These source parameter values were retained for further more complex field simulation and evaluation against measurements. Rectangular, small and medium sized off-set fields met the gamma-index criteria. For off-set fields greater than 15×15 cm2, the model failed the criteria at some dose points at the field edges. The jaws and MLC transmission parameters required adjustments for the irregular MLC field shapes comparisons. Conclusion The source model performed well and can be employed for dose verification ranging from simple regular fields to conformal treatments. In order to use the model for IMRT treatment verification, the model needs to be validated clinically. The only requirement is that Linac scatter factors must be measured separately to calculate the correct amount of monitor units necessary for patient treatment. Additional scatter sources can be implemented in the model to increase the accuracy at the field edges of the off-axis cases, which will require verification.

Lineêre versnellers produseer megavolt (MV) energie foton en elektron bundels om tumor volumes in pasiënte te bestraal. Meer komplekse behandelingsvelde kan vinnig opgestel word deur gebruik te maak van veelsegment kollimatore (VSK’s), om sodoende meer gevorderde behandelings, soos intensiteit-gemoduleerde bestraling (IGB), moontlik te maak. Dit is een van die redes waarom beplannings modelle so akkuraat as moontlik opgestel moet wees sodat akkurate dosis berekening algoritmes gebruik kan word. Monte Carlo (MC) gebaseerde dosis berekeninge is geskik om hierdie probleem op te los. Die doel van hierdie projek was om ‘n X-straal bron model verder te ontwikkel vir MC gebaseerde dosis berekeninge vir ‘n ElektaTM Precise VSK lineêre versneller. Metodes & Materiale ‘n Plaaslik ontwikkelde grafiese gebruikerskoppelvlak was gebruik om uitgangs tydvloed te bereken, wat gebaseer is op ‘n wiskundige model en energie spektra wat afgelei is vanaf die Schiff formule. Dit het ‘n invoer bron lêer geskep vir bron nommer 4 in die DOSXYZnrc kode. DOSXYZnrc was gebruik om X-straal dosis verspreidings in water en RW3 soliede water fantome te bereken. Hierdie dosis verspreidings was vergelyk met gemete film of watertenk dosis data. ‘n Gamma indeks was bereken om die MC en gemete dosis met mekaar te vergelyk. Die kriteria wat gebruik word vir die γ-indeks was 2 % dosis / 2 mm afstand-tot-ooreenkoms. Dosis verspreiding data vir vierkantige, reghoekige en ongesentreerde velde was vergelyk. Resultate & Bespreking Voordat die bron ingebruikneming begin is, is ‘n GAFCHROMIC® EBT2 film dosimetrie stelsel opgestel wat die gebruik van ‘n film skandeerder behels. Met die gebruik van die EBT2 film, is skandeerder eienskappe soos skandeerder eenvormigheid, film oriëntasie, film skanderings kant en herhaalbaarheid ondersoek. Film oriëntasie het die grootste verskil gelewer van 3.5 % tussen portret en landskap-oriëntasie. Die oorblywende eienskappe was binne 1 % variasie. ‘n Verskeidenheid van velde vir 6, 8 en 15 MV bundels was gemodelleer, gesimuleer en vergelyk met ooreenstemmende gemete watertenk data. Parameters in die MC bron model is aangepas totdat die gamma-indeks kriteria vir elke vergelyking bevredig is. Hierdie bron parameter waardes is behou vir verdere komplekse veld simulasies en ge-evalueer teen ooreenstemmende metings. Reghoekige, klein en medium grootte ongesentreerde velde het die gamma-indeks evaluering geslaag. Vir ongesentreerde velde groter as 15×15 cm2, het die model nie die evaluering geslaag by sekere dosis punte op die veldrandte nie. Die kollimator en VSK transmissie parameters het aanpassings vereis vir onreëlmatige VSK grootte velde wat vergelyk was. Gevolgtrekking Die bron model het goed presteer en kan gebruik word vir dosis bevestiging wat wissel van eenvoudige gereelde velde tot konforme behandelings. Dit is belangrik om die model klinies te toets en te bekragtig om die model vir IGB behandelings te bevestig. Die enigste vereiste is dat die lineêre versneller verstrooings faktore afsonderlik gemeet moet word sodat die korrekte aantal monitor eenhede bereken word wat nodig is vir pasiënt behandeling. Bykomende verstrooings bronne kan in die model geïmplementeer word om die akkuraatheid van die ongesentreerde gevalle te verhoog, wat verdere bevestiging gaan vereis.
Dissertation (M.Med.Sc. (Medical Physics))--University of the Free State, 2015
Keywords: Monte Carlo simulations; Linear accelerator; Multileaf collimators; GAFCHROMIC® EBT2 film; Intensity-modulated radiation therapy